Atypical symptoms with typical signs in a patient with Propionibacterium acnes related mitral valve endocarditis - Hameed, Rashid; Irrum, Noshine; Saxena, Pankaj; Musameh, Muntaser D. (International Journal of Research in Medical Sciences, 2021)
Infective endocarditis (IE) is a serious medical condition associated with an increase in morbidity and mortality if not treated promptly and adequately. The clinical outcome depends on the early diagnosis and aggressiveness of the causative organism. Patients usually present with typical features suggestive of Infective endocarditis but in some circumstances the presentations are atypical, and if not diagnosed and treated, may lead to serious consequences. We present a case of atypical presentations of infective endocarditis caused by Propionibacterium acnes organism with no classical features of endocarditis and had symptoms suggestive of urinary tract infection. The diagnosis of IE can be very difficult in patients with atypical clinical presentation, particularly caused by low-pathogenicity organisms. Appropriate clinical assessment and high level of suspicious especially in the patients with previous history of infective endocarditis or having prosthetic valves in situ is crucial.